Sea surface carbonate dynamics at reefs of Bolinao, Philippines: Seasonal variation and fish mariculture-induced forcing - Isah, Raffi R.; Enochs, Ian C.; San Diego-McGlone, Maria Lourdes (Frontiers in Marine Science, 2022)
Coral reefs are vulnerable to global ocean acidification (OA) and local human activities will continue to exacerbate coastal OA. In Bolinao, Philippines, intense unregulated fish mariculture has resulted in regional eutrophication. In order to examine the coastal acidification associated with this activity and the impact on nearby coral reefs, water quality and carbonate chemistry parameters were measured at three reef sites, a mariculture site and an offshore, minimally impacted control site during both the wet and dry season. Additionally, benthic community composition was characterized at reef sites, and both autonomous carbonate chemistry sampling and high-frequency pH measurements were used to characterize fine-scale (diel) temporal variability. Water quality was found to be poorer at all reefs during the wet season, when there was stronger outflow of waters from the mariculture area. Carbonate chemistry parameters differed significantly across the reef flat and between seasons, with more acidic conditions occurring during the dry season and increased primary production suppressing further acidification during the wet season. Significant relationships of both total alkalinity (TA) and dissolved inorganic carbon (DIC) with salinity across all stations may imply outflow of acidified water originating from the mariculture area where pH values as low as 7.78 were measured. This apparent mariculture-induced coastal acidification was likely due to organic matter respiration as sustained mariculture will continue to deliver organic matter. While TA-DIC vector diagrams indicate greater contribution of net primary production, net calcification potential in the nearest reef to mariculture area may already be diminished. The two farther reefs, characterized by higher coral cover, indicates healthier ecosystem functioning. Here we show that unregulated fish mariculture activities can lead to localized acidification and impact reef health. As these conditions at times approximate those projected to occur globally due to OA, our results may provide insight into reef persistence potential worldwide. These results also underscore the importance of coastal acidification and indicate that actions taken to mitigate OA on coral reefs should address not only global CO2 emissions but also local perturbations, in this case fish mariculture-induced eutrophication.